Conversion of lipid from food waste to biodiesel. (July 2015) - Karmee, Sanjib Kumar; Linardi, Darwin; Lee, Jisoo; Lin, Carol Sze Ki
Highlights: Lipid from food waste was used as a resource for the preparation of biodiesel. 100% biodiesel yield with KOH as catalyst at 1:10 lipid to methanol ratio in 2 h. 90% biodiesel yield at 40 °C and 1:5 lipid to methanol ratio using lipase in 24 h. Lipid to methanol ratio of 1:10 decreased in FAME yield due to deactivation of lipase. Abstract: Depletion of fossil fuels and environmental problems are encouraging research on alternative fuels of renewable sources. Biodiesel is a promising alternative fuel to be used as a substitute to the petroleum based diesel fuels. However, the cost of biodiesel production is high and is attributed mainly to the feedstock used which leads to the investigation of low cost feedstocks that are economically feasible. In this paper, we report on the utilization of lipid obtained from food waste as a low-cost feedstock for biodiesel production. Lipid from food waste was transesterified with methanol using base and lipase as catalysts. The maximum biodiesel yield was 100% for the base (KOH) catalyzed transesterification at 1:10 M ratio of lipid to methanol in 2 h at 60 °C. Novozyme-435 yielded a 90% FAME conversion at 40 °C and 1:5 lipid to methanol molar ratio in 24 h. Lipid obtained from fungal hydrolysis of food waste is found to be a suitable feedstock for biodiesel production.